Quality of life corrected by osteoarthritis of the hip and knee - therapeutic options for athletes - Dutka, Martyna; Bernacki, Piotr; Bernacki, Radosław; Zardzewiały, Witold; Zaremskyi, Oleksii; Białogłowski, Konrad; Skrzyńska, Klaudia; Mendyk, Krzysztof; Mordasiewicz, Dominika; Fuszara, Kamil (Quality in Sport, 2024)
Osteoarthritis (OA) is the most common chronic joint disease that causes slow degeneration of the articular cartilage of each joint component. For years, treatments have been sought to halt the progression of OA. Modern medicine has not yet found such a cure, but it has therapies to offer that make life more comfortable for a short period of time. Oral therapies with non-steroidal anti-inflammatory drugs and paracetamol effectively relieve only minor joint pain in the early stages of OA. Hyaluronic acid (HA) and corticosteroid (GCS) delivery therapies may result in clinically significant benefits in a significant number of patients, but emerging evidence suggests that the apparent efficacy of these treatments is largely due to other factors, including the placebo effect. The paucity of high-level evidence of action and methodological limitations make it difficult to consider delivery injections with stem cell preparations as effective in treating the causes of OA. Although many promising pharmacological treatments are currently in clinical trials, the best therapeutic option for OA to date is joint alloplasty. The most common surgical access when performing hip alloplasty is the posterior access. Replacing the diseased hip joint has many benefits for the patient including pain relief, improved quality of daily life and more efficient mobility.